KERUSAKAN TANAMAN PALA AKIBAT SERANGAN PENYAKIT BUSUK BUAH KERING DAN HAMA PENGGEREK BATANG PALA DI KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - A Marthin Kalay; Jacobus S. A. Lamerkabel; Frances J. L. Thenu (Jurnal Agroekoteknologi, 2015)
Fungus Stigmina myristicae causes rot dried fruit disease and pest Batocera herculesstem borer on nutmeg plants are found in Central Maluku, Province Maluku as the cause of plant damage nutmeg. Surveys in the District Laitutu Maluku Central was conducted in August 2014 with the aim to determine the intensity of the large and spacious dried fruit rot disease and stem borer, and the greater the intensity of dried fruit rot disease on various strata in the nutmeg crop. The results showed that the intensity of dried fruit rot disease is more prevalent in the nutmeg in the middle and lower strata of plants reached 1.42% and 2.09%, and in general to be 1.24%, while the area of the attack reached 23.90%. The intensity of the attacks stem borer reaches 1.76% and spacious attacks reached 0.56%. These results indicate that the nutmeg crop damage by Stigmina myristicae and Batocera hercules classified low category.Keywork:Stigmina myristicae, Batocera hercules,Nutmeg, Stem borer, Dried fruit rot.